2013
DOI: 10.1371/journal.pone.0054022
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Induces Anchorage Independence in 3T3 Cells and Detrimental Cytological Defects in an Infection Model

Abstract: Chlamydia are Gram negative, obligate intracellular bacterial organisms with different species causing a multitude of infections in both humans and animals. Chlamydia trachomatis is the causative agent of the sexually transmitted infection (STI) Chlamydia, the most commonly acquired bacterial STI in the United States. Chlamydial infections have also been epidemiologically linked to cervical cancer in women co-infected with the human papillomavirus (HPV). We have previously shown chlamydial infection results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…It has been well documented that C. trachomatis infection can lead to host cell multinucleation by disrupting host cytokinesis through disruption of furrow ingression or abscission [Greene and Zhong, ; Sun et al, ; Brown et al, ]. Moreover, a recent study has shown that C. muridarum can infect actively replicating host cells in a mouse model [Knowlton et al, ]. Our study is the first to demonstrate that there is a physiological benefit for C. trachomatis to block host mitosis.…”
Section: Discussionsupporting
confidence: 56%
“…It has been well documented that C. trachomatis infection can lead to host cell multinucleation by disrupting host cytokinesis through disruption of furrow ingression or abscission [Greene and Zhong, ; Sun et al, ; Brown et al, ]. Moreover, a recent study has shown that C. muridarum can infect actively replicating host cells in a mouse model [Knowlton et al, ]. Our study is the first to demonstrate that there is a physiological benefit for C. trachomatis to block host mitosis.…”
Section: Discussionsupporting
confidence: 56%
“…In the same line of evidence it was shown that infection of mice with C. trachomatis resulted in significantly increased cell proliferation, within the cervix, and in evidence of cervical dysplasia. 39 …”
Section: Discussionmentioning
confidence: 99%
“…induce anchorage- independent growth in mouse fibroblasts, a phenotype that correlates closely with tumorigenicity 119 . These phenotypes seem to be relevant in vivo as infection of the mouse cervix increases cervical cell proliferation, signs of cervical dysplasia and chromosome abnormalities 119 . Even eukaryotic cells that are cleared of Chlamydia spp.…”
Section: Modifying the Host Responsementioning
confidence: 98%